KEMENANGAN TAGORE ABUBAKAR PADA PILKADA BENER MERIAH ANALISIS PENDEKATAN MARKETING POLITIK - Maghfira Faraidiany; Hayatun Nufus; Annisah Putri (Halu Oleo University, 2025)
This article, titled “The Victory of Tagore Abubakar in the Bener Meriah Election: A Political Marketing Analysis”, aims to examine the factors contributing to this electoral success through a qualitative research approach. The study relies on secondary sources, including relevant literature and political marketing theories, to analyse the campaign strategies employed. The findings indicate that Tagore Abubakar’s victory was significantly influenced by the effective utilisation of social capital, political endorsements from major parties such as Gerindra and the Aceh Party (PA), and a well-crafted political marketing strategy. These strategies included emphasising his previous achievements in public office, promoting his commitment to the welfare of marginalised groups such as orphans and the poor and reinforcing his identity as a key figure in the movement for the creation of the Aceh Leuser Antara (ALA) region. Collectively, these elements shaped a strong political image that resonated with voters and led to widespread electoral support in Bener Meriah.